THE ROLE OF BEHAVIORAL SCIENCE IN PUBLIC ADMINISTRATION PROGRAMS. - Wyman, Sherman M.; Eddy, William B. (Public Administration Review)
The article presents information on the role of behavioral science in public administration programs. An understanding of the "human side" of organizational life is widely accepted as a significant aspect of the manager's role and a necessary topic of management education programs. Most masters' level programs in public administration or related areas offer some course work treating personnel relations and human behavior in organizations. Earlier approaches stressed awareness of existing human realities in organizational settings. The student was encouraged intellectually not to misunderstand or tread on them. More recently some programs have attempted to augment the theoretical descriptive approach by providing some applied behaviorial science methodologies for leadership, work design and training. These approaches assert an important difference between skill in intellectual analysis and competence in interpersonal relations. Understanding people is seen as quite different from being able to successfully play a change agent role, help two groups resolve conflict, or manage professionals in such a way that they develop organizational commitment among their own subordinates. Thus, the applied in applied behavioral science becomes significant and challenges some common conceptions about graduate education.